Oceans / Level 2 - Newbolt, Barnaby (Oxford : Oxford University Press, 2012)
Thousands of years ago, people looked out across an ocean and asked themselves, 'What is on the other side?' And the bravest of them began to travel and find the answers.. beautiful islands, frozen lands, different peoples. And there are still interesting questions about the oceans. Why does the water go up and down twice a day? Why do most animals and plants live near the land? And what can possible live at the bottom of the ocean, thousands of metres down, where there is no light? Surely nothing can stay alive in a place like that.
Included in the reader: Activities (Before reading ; While reading ; After reading).
Word count: 6,778.
Keywords: Readers (Adult); Readers for new literates; High interest-low vocabulary books; Graded Reader Level 2; Reading comprehension; Ocean